The effect of graphene flake size on the properties of graphene‐based polymer composite films. Issue 6 (6th September 2020) - Tarhini, Ali; Tehrani‐Bagha, Ali; Kazan, Michel; Grady, Brian
Abstract: In this work, the role of graphene flake size on the properties of poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP) composites was studied. Graphene flakes were added to PVDF‐HFP using a solution mixing and molding process. By increasing graphene particle size and its concentration in the composites, higher electrical conductivity, in‐plane thermal conductivity, and elastic modulus were achieved. Maximum tensile strength was obtained for the composites with average graphene flake size of 2, 5, and 7 μm at graphene concentrations of 10 wt%, 5 wt%, and 20 wt%, respectively. Thick flexible composite films (0.2–0.4 mm) with ultra‐high in‐plane electrical conductivity ( 4500 S/m), in‐plane thermal conductivity ( 26 W/m/K), and tensile strength ( 50 MPa) were obtained for the samples containing the graphene flakes with a larger average particle size of 7 μm. To our knowledge, the first two values are larger than any other values reported in the literature for PVDF‐based composites. Abstract :